Laser-induced toughening inhibits cut-edge failure in multi-phase steel. (1st March 2020) - Hoefnagels, J.P.M.; Du, Chaowei; Cem Tasan, C.
Abstract: The as-cut microstructures and the subsequent microstructural deformation characteristics of dual-phase steel specimens were analyzed using in-situ biaxial Marciniak tests, microscopic digital-image-correlation and nano-indentation, for two industrially relevant cutting processes: laser cutting and blanking. Interestingly, the strain-to-failure of the former is almost twice that of the latter, even though microstructural damage initiates twice as early (at 8% strain) in the ∼60 µm-thick, fully-martensitic surface layer of the laser-cut affected zone. However, its ∼145 µm-thick, tempered-martensite sub-surface layer provides the toughness to delay micro-damage propagation, arrest the crack growth, and ultimately provide the high strain-to-failure. These observations reveal guidelines to avoid cut-edge failure. Graphical abstract: Image, graphical abstract